Accountability of Licensing Service for Building Construction at the One-Stop Integrated Investment and Licensing Office of Ogan Ilir Regency - Siswanto, Joko; Suryani (HM Publisher, 2019)
The purpose of this research is to know the accountability services of building permission at the public of Investment and Integrated Licensing Service One Door of Ogan Ilir Regency. This type of research is qualitative research. The focus of the researched is the indicator of the accountability according to Dwiyanto (2012: 55). Data collection techniques used are by interview, observation and documentation. Data analysis technique used in this research is descriptive technique consisting of data reduction phase, data presentation and conclusion. The results of this study indicate that the accountability of building permission license services at the Public of Investment and Integrated Licensing One Door of Ogan Ilir Regency has not been fully accountable in providing services. Seen from the service reference is in accordance with the relevant local regulations. But in the implementation there are irrelevancy such as the length of service time and there's still an extra cost which must be spent by service users also the convoluted service requirements. Whereas seen from the service solutions provided by officers there have been improvements such as responses and better attitudes to the service users compared to previous years. Last seen from the interests of service users has been continuously made innovations towards service improvement such as with the surveys of services and management of feedback from service users is good enough. But it needs to be fixed is the action or development of new policies that need to be made so the service optimization could be achieved.